PENGARUH PEMBERIAN INSENTIF TERHADAP KINERJA KARYAWAN ( Kasus Pada Karyawan Bagian Produksi Pabrik Kelapa Sawit di PT. Rohul Sawit Industri Kabupaten Rokan Hulu Provinsi Riau) - Dialson Paulus; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to determine the effect of incentives on employee performance of the Production Department Palm Oil Factory PT. Rohul Sawit Industri. Providing incentives as the independent variable (X) has been formulated that is seen from the aspect of accuracy, feasibility Aspects / equity and financing aspects. While the employee's performance as the dependent variable (Y). This study was conducted on all employees of the Production Department Palm Oil Factory PT. Rohul Sawit Industri as many as 65 peoples.Data obtained from questionnaires and subsequently processed to then be tested using statistical analysis as a simple linear regression analysis, t test, and correlation analysis and determination using SPSS.The results showed that the hypothesis testing results thitung 11.205 t test> t table 1,998. This shows that the incentive effect on employee performance. The magnitude of the effect of incentives on employee performance of the Production Department Palm Oil Factory PT. Rohul Sawit Industri is 66.6%Keywords: Incentives, Employee Performance.